2013
DOI: 10.1186/1750-1172-8-132
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of specific anti-skin autoantibodies in a cohort of patients with inherited epidermolysis bullosa

Abstract: BackgroundInherited epidermolysis bullosa (EB) is a group of skin diseases characterized by blistering of the skin and mucous membranes.There are four major types of EB (EB simplex, junctional EB, dystrophic EB and Kindler syndrome) caused by different gene mutations. Dystrophic EB is derived from mutations in the type VII collagen gene (COL7A1), encoding a protein which is the predominant component of the anchoring fibrils at the dermal-epidermal junction.For the first time in literature, we have evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 40 publications
4
29
0
1
Order By: Relevance
“…Our findings extend what was reported by Tampoia et al who, studying serum concentrations of BP180, BP230 and COL7 antibodies, found that the levels were significantly higher in patients with RDEB than in EBS patients, and the values were correlated with EB severity [12]. In our study population, in addition to antibodies against BP180, BP230 and COL7, antibodies against DSG1 and DSG3 were evaluated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings extend what was reported by Tampoia et al who, studying serum concentrations of BP180, BP230 and COL7 antibodies, found that the levels were significantly higher in patients with RDEB than in EBS patients, and the values were correlated with EB severity [12]. In our study population, in addition to antibodies against BP180, BP230 and COL7, antibodies against DSG1 and DSG3 were evaluated.…”
Section: Discussionsupporting
confidence: 90%
“…Several hypotheses have been proposed to explain why, in inherited EB, an autoimmune mechanism aggravates the basal disease [12], but the precise triggers for the breakdown of self-tolerance and the subsequent events leading to the induction of pathogenic autoimmune responses remain undefined. Considering that children with the more severe EB phenotype usually have a greater number of skin infections, it could be supposed that an altered microbial diversity may cause a worsening of skin inflammation and autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ELISAs for Col7 are not highly specific as they may be positive in patients with Crohn disease or ulcerative colitis without cutaneous manifestations of EBA, atypical AIBD and patients with recessive dystrophic EB (RDEB) (Tables S5 and S6). Of note, the presence of circulating autoAbs against BP180, laminin 332 and the p200/laminin γ1 chain (detected by IB or ELISA), which may occur as a result of the epitope spreading phenomenon, does not rule out a diagnosis of EBA (supplementary cases 2 and 4 in Appendix S2). …”
Section: Resultsmentioning
confidence: 99%
“…We were intrigued by the presence of collagen VII in lymphoid conduits and strived to understand its function. The previously reported elevated humoral immunity in RDEB (32,33), together with the observation that the T-cell areas in spleen were devoid of collagen VII, suggested that absence of collagen VII may cause a specific impairment of innate antibacterial immunity. In the conduit basement membrane, collagen VII would interact with laminin 332 and collagen IV (SI Appendix, Figs.…”
Section: Collagen VII Physically Interacts With the Innate Immune Actmentioning
confidence: 94%